Ideology and Institutional Change: The Case of the English National Planning Policy Framework. (8th August 2021) - Shepherd, Edward
ABSTRACT: This paper deploys a discursive institutionalist framework to explore how various categories of ideas – from ideology, to programme, to policy – interact to shape the planning policymaking process. Using the emergence of the 2012 National Planning Policy Framework in England as a case study, the role of the political ideology of the leadership of a political party (as distinct from, but related to, the broader category of 'neoliberalism') in shaping and legitimising planning reform is analysed. It is shown that it is not only the political ideological legacy of a political party and how it melds with the prevailing paradigmatic orthodoxy (such as neoliberalism) that matters in framing planning reform, but that the way in which ideas are communicated and consulted on in the policymaking process is also significant.